From System Expansion to System Contraction. Access to Higher Education in Poland - Kwiek, Marek (My University, 2013)
The chapter explores access to higher education in Poland when demand-driven educational expansion is changing into educational contraction driven by demographic factors. It combines a theoretical framework with substantial original data analysis. The empirical evidence comes from educational statistics and statistical demographic projections. Educational expansion in Poland in 1995–2010 is related to four major dimensions: age, gender, sector (public/private) and status (full- and part-time). In addition, a section about access related to the intergenerational social mobility in Poland is based on microdata analysis of the EU SILC dataset (European Union Survey on Income and Living Conditions)– to explore the relative mobility of Polish society in Europe (in terms of educational attainment levels and occupational groups). The chapter contributes to academic discussions in four areas: global comparative research on private higher education (and related public/private dynamics), research on inter-sectoral and intra-sectoral differentiation of higher education, international comparative research on post-communist European higher education systems, and international comparative research on social stratification. The chapter refers to Poland and several post-communist European higher education systems which combine two features: a vast expansion following the fall of communism after 1989 and sharply falling demographics in the next two decades.
Keywords: educational expansion; educational contraction; Polish higher education; Polish universities; selectivity; equity; equitable access; demographics; EU-SILC; postcommunism; higher education; higher education reforms; Poland; private sector; demographic decline; demographic projections; intergenerational social mobility; private higher education; higher education policy; social stratification; European microdata; equality; social inequalities; access to higher education; public-private; Survey on Income and Living Conditions